Answer:
x = -
, x =
![(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/54kd5otoayi7fslqp2ejx77tdkhh8ubevy.png)
Explanation:
Given
2(6x² + 5x) = 12 ( divide both sides by 2 )
6x² + 5x = 6 ( subtract 6 from both sides )
6x² + 5x - 6 = 0 ← in standard form
(2x + 3)(3x - 2) = 0 ← in factored form
Equate each factor to zero and solve for x
2x + 3 = 0 ⇒ 2x = - 3 ⇒ x = -
![(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/810xodspel5mrswej0fay1vvz0sburw3kp.png)
3x - 2 = 0 ⇒ 3x = 2 ⇒ x =
![(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/54kd5otoayi7fslqp2ejx77tdkhh8ubevy.png)